Sexual Orientation Demographic Data in a Clinical Cohort of Transgender Patients - Dubin, Samuel; Cook, Tiffany E.; Radix, Asa; Greene, Richard E. (Applied Clinical Informatics, 2021)
Background There are specific issues regarding sexual orientation (SO) collection and analysis among transgender and nonbinary patients. A limitation to meaningful SO and gender identity (GI) data collection is their consideration as a fixed trait or demographic data point.Methods A de-identified patient database from a single electronic health record (EHR) that allows for searching any discrete data point in the EHR was used to query demographic data (sex assigned at birth and current GI) for transgender individuals from January 2011 to March 2020 at a large urban tertiary care academic health center.Results A cohort of transgender individuals were identified by using EHR data from a two-step demographic question. Almost half of male identified (46.70%, n = 85) and female identified (47.51%, n = 86) individuals had “heterosexual/straight” input for SO. Overall, male and female identified (i.e., binary) GI aggregate categories had similar SO responses. Assigned male at birth (AMAB) nonbinary individuals (n = 6) had “homosexual/gay” SO data input. Assigned female at birth (AFAB) nonbinary individuals (n = 56) had almost half “something else” SO data input (41.67%, n = 15). Individuals with “choose not to disclose” for GI (n = 249) almost all had “choose not to disclose” SO data (96.27%, n = 232).Conclusion Current SO categories do not fully capture transgender individuals' identities and experiences, and limit the clinical and epidemiological utility of collecting this data in the current form. Anatomical assumptions based on SO should be seen as a potential shortcoming in over-reliance on SO as an indicator of screening needs and risk factors.
Keywords: sexual orientation; gender identity; transgender; electronic health record